RESPON SISWA TERHADAP PENGGUNAAN MODUL TEMATIK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Ummu Khairiyah; Silviana Nur Faizah (Universitas Islam Malang, 2020)
This research aimed to determine students' responses to the use of thematic modules based on the integration of Islam and science in improving critical thinking skills on energy themes and their changes in 3rd grade MI Salafiyah Kutukan Blora. The research method apply in this research is descriptive research. The Descriptive research used in this research is the survey. The research instrument used was a student response questionnaire. Analysis of student response questionnaires showed that 80,3% of students stated that using thematic modules could improve students' critical thinking skills